2016
DOI: 10.1016/j.cell.2016.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Full-Length Human Tetraspanin Reveals a Cholesterol-Binding Pocket

Abstract: SUMMARY Tetraspanins comprise a diverse family of four-pass transmembrane proteins that play critical roles in the immune, reproductive, genitourinary, and auditory systems. Despite their pervasive roles in human physiology, little is known about the structure of tetraspanins or the molecular mechanisms underlying their various functions. Here we report the crystal structure of a full-length tetraspanin, human CD81. The transmembrane segments of CD81 pack as two largely separated pairs of helices, capped by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
330
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(356 citation statements)
references
References 66 publications
(74 reference statements)
25
330
1
Order By: Relevance
“…The stoichiometry of the E2-CD81 interaction in vivo is unknown, although there is evidence that CD81 forms a dimer at the cell surface (46,47). However, a recent structure of full-length CD81 reported a monomer and suggests that the observed dimeric structure of the isolated CD81-LEL may be nonphysiological (48,49). Our in vitro analysis indicated that the E2 homodimer has a 1:1 binding stoichiometry with a recombinant, dimeric form of CD81-LEL, compared with a 2:1 ratio for the monomer, suggesting that the Δ123 homodimer has two CD81-LEL competent binding sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stoichiometry of the E2-CD81 interaction in vivo is unknown, although there is evidence that CD81 forms a dimer at the cell surface (46,47). However, a recent structure of full-length CD81 reported a monomer and suggests that the observed dimeric structure of the isolated CD81-LEL may be nonphysiological (48,49). Our in vitro analysis indicated that the E2 homodimer has a 1:1 binding stoichiometry with a recombinant, dimeric form of CD81-LEL, compared with a 2:1 ratio for the monomer, suggesting that the Δ123 homodimer has two CD81-LEL competent binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports that the CD81 receptor adopts a dimeric structure at the cell surface (46,47), and solved structures of recombinant CD81-LEL also describe a homodimer (48). However, a recently reported structure of full-length CD81 depicts a monomer in which the LEL dimerization interface is within 3.5 Å of the TM1/TM2 bundle, suggesting that the LEL homodimer is the result of lattice packing effects in the absence of the TM domains (49). However, the stoichiometry of binding between E2 and CD81 is unknown.…”
Section: The Hcv E2 Core Adopts a Functional Homodimermentioning
confidence: 97%
“…These studies demonstrated that the EC2 domain of tetraspanins consist of one conserved and one variable domain, with the conserved domain consisting of a three-helix bundle while the variable domain is unique to particular tetraspanins. A recent report resolved a crystal structure of full-length CD81, finding that the four transmembrane domains create a cholesterol-binding pocket (Zimmerman et al, 2016). Furthermore, the authors performed molecular dynamics simulations that suggest CD81 can adopt an open or closed conformation depending on whether or not cholesterol is bound.…”
Section: Introductionmentioning
confidence: 99%
“… Schematic of tetraspanin molecular structure (Based on Zimmerman et al, 2016) . Cartoon depicting the structural characteristics of tetraspanins.…”
Section: Introductionmentioning
confidence: 99%
“…It looks mushroom-shaped and it consists of a conserved subdomain, including three helices and a more variable one with two helices, possibly involved in the binding to other membrane proteins (Kitadokoro et al, 2001; Seigneuret et al, 2001). The full CD81 structure revealed a cone-like structure, where the LEL harbors an intramembrane cavity which is supposed to bind cholesterol (Zimmerman et al, 2016). It is speculated that the cholesterol bound structure favors a closed structural state of this tetraspanin with less tightly bound partner proteins.…”
Section: What Are Tetraspanins?mentioning
confidence: 99%